Vaccination in drugstores: legal aspects and the role of the pharmaceutical professional (Research, Society and Development, 2022)
The emergence of the vaccine occurred after an outbreak of smallpox that started in the silk region between China and Turkey. In Brazil, in 1904, Rio de Janeiro faced a smallpox epidemic that resulted in the Vaccine Uprising. Vaccination services are offered in Basic Health Units (BHU), which was also extended to private pharmacies and drugstores through the Federal Pharmacy Council Resolution No. 574 of May 22, 2013.  The objective of the present study was to describe how pharmacies and drugstores can develop and apply the vaccination service for the population. This is descriptive research of qualitative nature. For data collection it was performed searches in the databases of Science direct, Pubmed, Scielo through the journals of CAPES (Coordination for the Improvement of Higher Education Personnel), as well as the legislation of the CFF (Federal Pharmacy Council) and ANVISA (National Health Surveillance Agency). It was observed that pharmacies and drugstores that wish to expand their pharmaceutical services through vaccination need to pay attention to several items that are mandatory: licensing of the health agency; physical structure suitable for the demand; quality inputs and especially the pharmacist professional qualified for this service, which must be proven through the CFF to which he belongs.